Shipboard Safety Familirization, Langkah Awal Manajemen Keselamatan Bekerja Di Atas Kapal - Wahyudi Santoso; Kholid Mawardi; Yulianto Yulianto (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
One of the uniqueness and challenges of seafarers in working on a ship is transferring from one ship to another, where each ship is different so that the risks or dangers of each ship also vary. The purpose of this research is to find out the initial steps for seafarers who have just joined work, so that they are familiar with their new ship (safety equipment, equipment and work procedures, etc.) as well as the potential dangers that may occur including alarms, tasks and actions in dealing with these distress situations. The research uses a literature review method, with references to national and international regulations in the maritime sector, maritime publications, journals, books and other relevant sources. The results of the research, Shipboard Safety Familiarization is an obligation that must be given to crew members who have just joined a ship, even though by standard Seafarers before working on a ship already have knowledge and skills related to safety equipment, firefighting, medical, effective communication, and distress conditions. (from alarms, fastest refugee routes, to actions that must be implemented). Familiarization is provided by the Captain or appointed Officer and the Crew they replace regarding safety equipment and work equipment, Duties and Responsibilities according to position and when there is a Danger situation, rules and decisions regarding Work Safety and Security of the Company that operates the ship with a gradual duration of time